Qual o impacto da pesca de arrasto sobre a assembleia de camarões em áreas costeiras marinhas? Uma análise temporal de populações a ecossistema no litoral norte de São Paulo - Perroca, Júlia Fernandes [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Different life cycles lead to differences in species niche and in their ecological requirements. In this study we registered the spatial and temporal variance in abundance in eight shrimp species by analyzing a dataset that spanned a 27-year period. We also assessed the influence of ocean-climatic and environmental factors in their abundance. Periods of neutrality favored the increase in abundance of Artemesia longinaris, Pleoticus muelleri, Rimapenaeus constrictus, Sicyonia dorsalis and Nematopalaemon schmitti. The shrimps P. muelleri and S. dorsalis also showed higher abundances in periods of La Niña. In La Niña and neutral periods, there is a shift in the atmospheric pressure gradient favoring Northeast winds, that enhances the SACW intrusion and weakens the Coastal Water. Thus, species that responds negatively to elevated temperatures, as P. muelleri and S. dorsalis, in El Niño will migrate to deeper areas, which were not sampled in this study. As for El Niño events, it favored the abundance of Litopenaeus schmitti and R. constrictus. El Niño is known to increase water surface temperature in southeast Brazil, so the increase in temperature is benefic to these species whose abundances increase in elevated temperatures. All species were associated with sediments of silt and clay. Long-term monitoring of the communities of species of commercial interest or accidentally captured, are essential for establishing standards and measures to protect ecosystems.

Diferentes ciclos de vida levam a diferenças no nicho das espécies e em seus requerimentos ecológicos. Neste estudo, registramos a variação espacial e temporal da abundância em oito espécies de camarão, analisando um conjunto de dados que abrangeu um período de 27 anos. Também avaliamos a influência de fatores oceânico-climáticos e ambientais em sua abundância. Períodos de neutralidade favoreceram o aumento da abundância de Artemesia longinaris, Pleoticus muelleri, Rimapenaeus constrictus, Sicyonia dorsalis e Nematopalaemon schmitti. Os camarões P. muelleri e S. dorsalis também apresentaram maior abundância em períodos de La Niña. Nos períodos de La Niña e neutro, há uma mudança no gradiente de pressão atmosférica favorecendo os ventos de Nordeste, que fortalece a intrusão da ACAS e enfraquece a Água Costeira. Assim, espécies que respondem negativamente a temperaturas elevadas, como P. muelleri e S. dorsalis, no El Niño irão migrar para áreas mais profundas, que não foram amostradas neste estudo. Já o El Niño favoreceu a abundância de Litopenaeus schmitti e R. constrictus. El Niño é conhecido por aumentar a temperatura da superfície da água no sudeste do Brasil, então o aumento da temperatura é benéfico para essas espécies cuja abundância aumenta em temperaturas elevadas. Todas as espécies foram associadas a sedimentos de silte e argila. O monitoramento de longo prazo das comunidades de espécies de interesse comercial ou capturadas acidentalmente, é essencial para o estabelecimento de padrões e medidas de proteção dos ecossistemas.
What is the impact of trawling on shrimp assemblage in marine coastal areas? A temporal analysis of populations and ecosystems on the northern coast of São Paulo
Keywords: SACW; Bycatch; Caridea; Decapoda; ENSO; Penaeoidea